Get the most out of your questions with IDNLearn.com's extensive resources. Our platform provides accurate, detailed responses to help you navigate any topic with ease.
Sagot :
Answer:
y= -11
Step-by-step explanation:
After rearranging equation 2, we get x= y+3/2
Sub it into equation 1
y= 3(y+3/2) + 1
y= 3y+9/2 + 1
y= 3y + 11 / 2
2y = 3y + 11
-y = 11
y = -11
The answer is D. -11
-3x+1=2x-3 (solve and you will get x= -4)
Substitute x in one of the equations to solve for x
y= 3(-4) + 1
y= -11
-3x+1=2x-3 (solve and you will get x= -4)
Substitute x in one of the equations to solve for x
y= 3(-4) + 1
y= -11
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. Find clear answers at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.